Intelligent planning method for large-scale low-orbit constellation supplementary network. Issue 1 (April 2021) - Cui, Wenhui; Zhang, Zhibin; Cao, Xiaolong; Zhao, Xiangwen; Sun, Jingfeng
Abstract: Large LEO constellations have become increasingly prominent in the aerospace field. When some satellites in the constellation fail, the traditional SOC (Streets-of-Coverage) constellation coverage analysis method can no longer evaluate the coverage of the constellation accurately. A method for calculating the space coverage performance of the large constellation with an incomplete configuration using a single-satellite space coverage stacking method is deduced. The constellation TT&C (Telemetry Tracking and Command) planning method based on spatial coverage assessment is proposed. The genetic algorithm is taken to illustrate the general steps of the intelligent planning of constellation complementary network, and the intelligent planning model design for multiple constellation TT&C restriction and covering the optimal target is realized.